Cover - Studio, Magno; Carara, Jacqueline (Brazilian Dental Science, 2017)
Figure of the article:: Benign fibrous histiocytoma of the tongue: a case report;.Authors: Michele Fonseca BRANTES, Rebeca de Souza AZEVEDO, Silvia Paula de OLIVEIRA, Adriele Ferreira GOUVÊA, Ademar TAKAHAMA JR